My best friend’s doctor’s appointment: A social anthropological study on the restoration of dolls and stuffed animals by and for adults - Whitt,Frederikke (2025)
This thesis analyzes how and why old toys are restored by and for adults, despite contemporary Western society's understanding of toys as signifiers of childhood exclusively. With this in mind, the intent is to answer whether childhood attachments to toys can also be observed in adults by analyzing how the restoration process of toys reaffirms emotional and social significance for all involved in the restoration process. Empirical data was collected through five primary semi-structured interviews. Two of these were done by people who have established toy restoration businesses. Data was also collected through participant observation at a miniature toy fair and through video analysis and discourse analysis of social media content on TikTok and Facebook. This data was analyzed using the concepts of material culture, social anthropology, and psychological theories related to transitional objects, memory objects, and biographical objects, as well as previous research on adult attachments to childhood objects and repair work. The study shows that childhood attachments to toys can also be observed among adults due to childhood memory, family bonds, and the objects as sources of comfort. These factors influence how toys are interacted with during the restoration process and how the restoration affects the interaction between restorers and customers.
Keywords: Social anthropology; material culture; memory; emotions; childhood objects